Hakikat Filsafat Ilmu Pendidikan: Landasan Teoritis dan Praktis dalam Pengembangan Sistem Pendidikan Modern - Muhammad Zia-ulHaq,; Abdullah Sinring; Syamsu Kamaruddin (Universitas Muhammadiyah Gresik, 2024)
The philosophy of educational science serves as a critical framework for understanding the theoretical and practical foundations of education. This research explores the nature of the philosophy of educational science with a focus on the dimensions of epistemology, ontology, and axiology. With a qualitative approach, this research examines how philosophical insights contribute to the development of inclusive, ethical, and innovative educational practices. The research findings emphasize the need to align educational goals with societal values while also addressing the conflict between traditional paradigms and the demands of contemporary education. This research provides a strong theoretical foundation for the development of a transformative education system in the 21st century.